1993
DOI: 10.1042/bj2900419
|View full text |Cite
|
Sign up to set email alerts
|

Purified hybrid insulin/insulin-like growth factor-I receptors bind insulin-like growth factor-I, but not insulin, with high affinity

Abstract: Hybrid insulin/insulin-like growth factor-I (IGF-I) receptors have previously been described in human placenta, but it has not been possible to study their properties in the presence of classical insulin receptors and type I IGF receptors. To facilitate the purification of hybrids, we produced an anti-peptide monoclonal antibody IGFR 1-2, directed against the C-terminal peptide of the type I IGF receptor beta-subunit. The antibody bound native human and rat type I IGF receptors, and reacted specifically with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
165
0
1

Year Published

1996
1996
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 256 publications
(177 citation statements)
references
References 66 publications
11
165
0
1
Order By: Relevance
“…This partial rescue of the action of insulin on glucose storage and in vivo insulin signalling by impaired insulin clearance is likely to involve an effect of higher insulin levels on the fraction of fully functional (wt/wt) insulin receptors. Additionally, insulin levels of ∼1,300 pmol/l may be enough to overcome the ∼10-fold lower affinity of insulin for IGF-I and insulin/IGF-I hybrid receptors and evoke signalling through these receptors [24]. Reports of an increased number of insulin/IGF-I hybrid receptors in muscle of patients with chronic hyperinsulinaemia [25,26] provide further support for a potential compensatory action of insulin through the IGF-I receptors in patients with mutant INSR.…”
Section: Discussionmentioning
confidence: 99%
“…This partial rescue of the action of insulin on glucose storage and in vivo insulin signalling by impaired insulin clearance is likely to involve an effect of higher insulin levels on the fraction of fully functional (wt/wt) insulin receptors. Additionally, insulin levels of ∼1,300 pmol/l may be enough to overcome the ∼10-fold lower affinity of insulin for IGF-I and insulin/IGF-I hybrid receptors and evoke signalling through these receptors [24]. Reports of an increased number of insulin/IGF-I hybrid receptors in muscle of patients with chronic hyperinsulinaemia [25,26] provide further support for a potential compensatory action of insulin through the IGF-I receptors in patients with mutant INSR.…”
Section: Discussionmentioning
confidence: 99%
“…Hybrid receptors consisting of one αβ-subunit from the IGF-IR and one αβ-subunit from the IR occur and functions mainly as an IGF-IR with approximately 20-fold higher affinity for IGF-I than for insulin (18). Insulin/IGF-I hybrid receptors have been found in several different human tissues, as muscle, fat, kidney (19) and human cell types, including different breast cancer cells (20) and endothelial cells (21,22).…”
Section: Introductionmentioning
confidence: 99%
“…It is interesting that only IR and insulin-like growth factor-1 receptor (IGF-1R) adopt such complex structures in the extracellular domain for regulating the signaling (Ullrich et al 1986). Previously, it was reported that IR and IGF-1R can form an IR/IGF-1R hybrid receptor (HR) which is activated by IGF-1/2 (Soos et al 1990(Soos et al , 1993. Of note, IGF-1/2 induces proliferation not only in normal cells but also in cancer cells such as breast and thyroid carcinomas, where HR formation has been confirmed Pandini et al 1999).…”
Section: Discussionmentioning
confidence: 96%